Janet Charman’s "cold snack" - White, M (Auckland University Press, 2008)
Book Design: Cover design and photographic images: "St Jude's Crossing". Plus section title photographic images: One, Two and Three, from "All the Numbers from 1 to 96"
Keywords: Book Design; Photography